2005
DOI: 10.1002/bit.20563
|View full text |Cite
|
Sign up to set email alerts
|

Use of the chicken lysozyme 5′ matrix attachment region to generate high producer CHO cell lines

Abstract: Scaffold or matrix attachment region (S/MAR) genetic elements have previously been proposed to insulate transgenes from repressive effects linked to their site of integration within the host cell genome. We have evaluated their use in various stable transfection settings to increase the production of recombinant proteins such as monoclonal antibodies from Chinese hamster ovary (CHO) cell lines. Using the green fluorescent protein coding sequence, we show that S/MAR elements mediate a dual effect on the populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(93 citation statements)
references
References 39 publications
4
88
1
Order By: Relevance
“…The FVII expression amount in the selected CHO-K1 cell line was determined to be approximately 300 ng/mL. These results suggest that the construction of vectors (Girod et al, 2005;Wang et al, 2008) should be used in future research to increase the copy number in CHO-K1 cells and thereby improve expression levels.…”
Section: Discussionmentioning
confidence: 87%
“…The FVII expression amount in the selected CHO-K1 cell line was determined to be approximately 300 ng/mL. These results suggest that the construction of vectors (Girod et al, 2005;Wang et al, 2008) should be used in future research to increase the copy number in CHO-K1 cells and thereby improve expression levels.…”
Section: Discussionmentioning
confidence: 87%
“…Insulators are known to protect genes within a chromatin domain from stimulatory or repressive effects of flanking genomic regions (Antes et al 2001;Bode et al 2000;Namciu et al 1998). In addition, Girod et al (2005) showed that an insulating element, MAR, improved the transgene expression in stable producing cells. To determine the insulating activity of UR, we generated HEK293, HeLa, and CHO-K1 stable cells, which contain stably integrated CMV plasmids.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, UR has been shown to act as an insulator (Angulo et al 2000;Lashmit et al 2004;Lundquist et al 1999). Insulating elements, such as nuclear matrix-associated regions (MARs), can enhance recombinant protein expression in stably integrated cell lines (Girod et al 2005;KohwiShigematsu et al 1997). Therefore, CMV UR could also be a positive element of CMV MIE promoter.…”
Section: Introductionmentioning
confidence: 99%
“…To minimize the influence of this position effect, cis-acting barrier elements, called insulators that block the propagation of a heterochromatin structure into neighboring euchromatin regions, have been incorporated into the expression vector to isolate the integrated transgene from nearby negative influences in the case where the vector is integrated into a condensed chromosomal region (Ghirlando et al 2012). The use of such insulating elements significantly increases the number of producing clones and improves the recombinant protein titer (Girod et al 2005;Boscolo et al 2012;Hou et al 2014).…”
Section: Vectors and Modulation Of Transgene Expressionmentioning
confidence: 99%